A dryinid wasp in Early Eocene amber from the Paris basin (Hymenoptera: Dryinidae) - Peinado, Julie; Waller, Alain; Waller, Alain (Zootaxa, 2006)
Pseudodryinus parisiensis sp. n., is described from the Earliest Eocene French amber. The potential relationships of the new species are discussed. The present discovery supports the important differences between the French and Baltic Eocene ambers.